El ecosistema de los emprendimientos sociales liderados por mujeres: un estudio fenomenológico en Perú - Palmer Torres, Jussara Inez Anaí (2025)
Purpose. This study employs a phenomenological methodology to examine the experiences of women leaders in the Peruvian social entrepreneurship ecosystem. It investigates the ecosystem dimensions, the creation of social enterprises, the facilitators and barriers that women must face, and the role that social entrepreneurship. Desing/methodology/approach. The sample comprised 30 peruvian women who are founders, owners, and leaders of social enterprises. Data were gathered through in-depth interviews, which were coded, categorized, and analyzed following Moustakas's (1994) methodology. Findings. The study proposes an analytical framework for understanding women’s experience in the social entrepreneurship ecosystem, which includes a mapping of actors, ecosystem dimensions, the initiation and development of womenled social enterprises, highlighting individual, social, cultural, and institutional factors. It also explores the facilitators and barriers in social entrepreneurship and the role these enterprises play in the lives of their leaders and society, along with the resources they utilize. Originality/value. The results offer valuable insights for authorities and policymakers working to promote entrepreneurship ecosystems. The uniqueness of this study lies in its investigation in Peru, a country with the highest female labor force participation in Latin America, ranking fourth in entrepreneurial intent in Latin America and eighth globally (Global Entrepreneurship Monitor Peru, 2018-2019).